Odpowiedzi

2010-03-09T11:32:26+01:00
(x+4)²-(x-5)²-(x-1)²=14x-1
x²+8x+16-x²+10x-25-x²+2x-1=14x-1
-x²+6x-9=0

Δ=b²-4ac=36-36=0

x=-b:2a=-6:-2=3
x=3

spr. (3+4)²-(3-5)²-(3-1)²=14×3-1
49-4-4=42-1
41=41
2010-03-09T11:33:02+01:00
(x+4)²-(x-5)²-(x-1)²= 14x-1
x²+8x+16-x²+10x-25-x²+2x-1=14x-1
-x²+6x=9

Δ=b²-4ac=36-36=0
x=-b:2a=-6:-2=3
x=3
2010-03-09T11:39:25+01:00
(x+4)²-(x-5)²-(x-1)²= 14x-1
x²+8x+16-(x²-10x+25)-(x²-2x+1)=14x-1
x²+8x+16-x²+10x-25-x²+2x-1=14x-1
-x²-6x=9
-x²-6x-9=0
a=-1 b=-6 c=-9
Δ=b²-4ac
Δ=36-36
Δ=0
x1=-b-√Δ/2a=3
x2=-b+√Δ/2a=3
x=3